Changes in the social architecture of business model in the perspective of the Industry 4.0 concept - Grabowska, Sandra (Zielona Góra: Faculty of Economics and Management Press)
After three industrial revolutions, the fourth comes, which transfers production to sophisticated networks of companies equipped with intelligent devices, machines, means of transport, communicating with each other using modern technologies. It creates new challenges for industrial enterprises, it requires redefining existing business models.
Keywords: industrial revolution; business model; Leader 4.0; Industry 4.0; rewolucja przemysłowa; model biznesu; Lider 4.0; Przemysł 4.0